The organic artist : make your own paint, paper, pens, pigments, prints, and more from nature - Neddo, Nick. (Beverly, MA : Quarry Books, 2015)
"It's time to go back to basics! If you're interested in art, but find that it's becoming an increasingly expensive hobby, The Organic Artist is just the book for you! It encourages us all to return to those days when art was made with all-natural materials, such as charcoal and birch bark. Immersing you in the natural world, The Organic Artist seeks to inspire creativity by connecting you to your organic roots. In addition to offering a wide variety of suggestions for using nature as supplies for art, this book also introduces the concepts of awareness and perception that are foundational to the creative process. Readers will refine drawing skills, as well as increase their appreciation for the visual arts and the natural landscape. Some of the projects and skills covered include the following: making paper and wild ink, working with soapstone, clay, wood, and rawhide, printmaking and stenciling, natural pigments and dyes, camouflage and body painting, and nature journaling"--
boek